A hybrid crow search algorithm to minimise the weighted sum of makespan and total flow time in a flow shop environment. (2018) - Marichelvam, M.K.; Geetha, M.
In this paper, flow shop scheduling problems which were proved to be strongly NP-hard (non-deterministic polynomial time hard) are considered. The objective is to minimise the weighted sum of makespan and total flow time. For solving this problem, a recently developed meta-heuristics algorithm called as crow search algorithm is proposed. Moreover, the dispatching rules are hybridised with the crow search algorithm to improve the solution quality. An evaluation of the performance of the proposed algorithm is carried out by industrial scheduling problem and the results are compared with many dispatching rules and constructive heuristics. The results obtained by the proposed algorithm are much better than the dispatching rules and constructive heuristics. Random problem instances are also used to validate the performance of the proposed algorithm. The results are compared with many other meta-heuristics addressed in the literature and the results indicate the effectiveness of the proposed algorithm in terms of solution quality and computational time. To the best of our knowledge this is the first reported application of crow search algorithm to solve the scheduling problems.